A Small Group Randomized Double-Blind Placebo-Controlled Study to Evaluate the Efficacy of Daily Pentoxifylline in the Management of Patients With Erectile Dysfunction with Suboptimal Treatment Response to Sildenafil - Law, Y.X.T. (Elsevier B.V., 2021)
10.1016/j.esxm.2019.08.012